Comparing outcomes in patients with end-stage chronic obstructive pulmonary disease: single versus bilateral lung transplants. (25th June 2021) - Mutyala, Sudeep; Kashem, M Abul; Kanaparthi, Jay; Sunagawa, Gengo; Suryapalam, Manish; Leotta, Eros; Minakata, Kenji; Brann, Stacey; Shigemura, Norihisa; Toyoda, Yoshiya
Abstract: : OBJECTIVES: Debate continues on whether a bilateral (BLT) or a single lung transplantation (SLT) is preferred for patients with end-stage chronic obstructive pulmonary disease (COPD). The purpose of this study is to examine the interplay between patient age and transplant type on survival outcomes. METHODS: We performed a retrospective study of lung transplants for COPD at our centre from February 2012 to March 2020 ( n = 186). Demographics and clinical parameters were compared between patients based on their age (≤65 vs >65 years old) and type of transplant (single vs bilateral). Cox proportional hazards regression was also performed. P -values <0.05 were considered significant. RESULTS: Of the 186 patients with COPD who received lung transplants, 71 (38.2%) received BLTs and 115 (61.8%) received SLTs. There was no significant difference in survival outcomes when looking at patients with single versus BLTs ( P = 0.870). There was also no difference in survival between the 2 age groups ≤65 versus > 65 years ( P = 0.723). The Cox model itself also did not show a statistically significant improvement in survival outcomes ( P = 0.126). CONCLUSIONS: Lung transplant outcomes in patients with end-stage COPD demonstrated non-inferior results in patients with an SLT compared to patients with a BLT. When we compared the age groups, neither transplant type showed superior survival benefits, suggesting there may be some utility in an SLT in younger recipients. Abstract : Chronic obstructive pulmonary disease (COPD) with end-stage disease remains a major indication for a lung transplant, accounting for over a third of all lung transplants globally [1].